The effect of foliar spraying with humic acid and anti-transpiration Nautilus on the vegetative growth characteristics of local lemon trees. - Shahlaa Ali Madloom; Falah Hassan Al-Mayahi (University of Thi-Qar Journal of agricultural research, 2025)
This study was conducted in one of the private orchards affiliated to Al-Nasr District in Dhi Qar Governorate for the year 2024-2025. To study the effect of foliar fertilization with humic acid at three levels (0, 1.5, 3) g. L-1 and spraying with anti-transpiration (Nautilus) at three levels (0, 1, 2) ml. L-1 on the vegetative growth characteristics of local lemon trees. The results obtained can be summarized as spraying with humic acid at the level of (3 g. L-1) had a significant effect on the vegetative characteristics of the plant (leaf area, stem diameter, number of leaves, number of branches, plant length) compared to the comparison coefficient. Likewise, spraying with Nautilus at the level of (2 ml. L-1) had a clear significant effect on the vegetative characteristics studied for local lemon trees compared to the comparison coefficient. The two-way interaction between the study treatments had a clear significant effect on the H2I2 treatment (3 g/L-1 x 2 ml/L-1) in most of the studied traits.